Magnesium (Mg) for Citrus Trees - Mongi Zekri; Tom Obreza (EDIS)
Magnesium deficiency has been a major problem in citrus production. In Florida, Mg deficiency is commonly referred to as “bronzing.” Trees with inadequate Mg may have no symptoms in the spring growth flush, but leaf symptoms develop as the leaves age and the fruit expand and mature in the summer and fall. Magnesium deficiency symptoms occur on mature leaves following the removal of Mg to satisfy fruit requirements. This 4-page fact sheet was written by Mongi Zekri and Tom Obreza and published by the UF Department of Soil and Water Science, July 2013.